INSOMNIA : SUATU ANALISIS TERHADAP FAKTOR PENYEBAB, DAMPAK DAN PENANGANANNYA - Dian Budianti; Shinta Brisma (Yayasan Nusantara Hasana Berdikari, 2025)
Insomnia is a sleep disorder characterized by difficulty falling asleep, trouble staying asleep, or waking up too early and being unable to return to sleep. This disorder can negatively affect a person's quality of life, including decreased concentration, reduced productivity, and an increased risk of physical and mental health issues. Insomnia can be caused by various factors, such as stress, unhealthy lifestyle habits, psychological disorders, and certain medical conditions. This study aims to analyze the causes of insomnia, its impact on health, and possible management strategies. The research method used is a literature review examining various scientific sources related to insomnia. The results show that insomnia management can be done through lifestyle changes, cognitive-behavioral therapy, and medication in certain cases. Awareness of the importance of quality sleep and the implementation of good sleep habits can help reduce the risk of insomnia and improve individual well-being.